Application of UAV in shoreline detection - Mohd Salleh, Anuar (Penerbit UTHM, 2021)
Shoreline is defined as the interface between the land and the sea and the immediate position of the land-water line at one instant in time. This is because of the active nature of water bodies and the coastal land, the shoreline constantly changing (Paterson et. al, 2010). Shoreline change depicts how the position of the shoreline moves with time. Several studies point out that two main factors that can be responsible for changing the shoreline are human activities along the shore or natural processes. An example of a natural process can be a sea-level rise, change from storms and climate extreme weather events, including an increase in the intensity and frequency of waves on the shoreline face and beaches. Shorelines can also move landwards through the process of erosion; or seawards by sediment accretion. Shoreline change can also be used as a good indicator of possible coastal erosion and the best indicator for describing coastal erosion is the shoreline retreat rate. This phenomenon can be detected by using the latest technology such as Unmanned Aerial Vehicle (UAV).